TOO MUCH INFORMATION? EXPLORING THE ROLE OF 'INFORMATION BURDEN' IN THE EXPERIENCES OF CAREGIVERS FOR OLDER ADULTS. (11th November 2018) - Mirza, R; Hsieh, J; Klinger, C
Abstract: With the onus of care for the elderly shifting onto informal caregivers, older adults may often be accompanied by family caregivers to medical visits. In order to optimize care and to participate in healthcare decision-making for the older patient, caregivers are often privy to significant health information. This may include personal details about the patient previously unknown to the caregiver, information about advance care and end-of-life planning, and a 'bad news' diagnosis. However, a commonly overlooked issue in geriatric practice is the amount of information that caregivers must acquire and manage as patients get older and more dependent on them. Caregivers, often deemed the 'invisible second patient', may feel inundated with the health information shared and feel unprepared, vulnerable and in need of healthcare support themselves. Using a qualitative research design, 49 in-depth interviews with 23 caregivers of older adults were conducted over a year. Our results illustrate how caregivers often provide care and conceal information from loved ones at the detriment to their own health and social well-being. Interview data highlights the complexity of managing health information with some gender differences in caregiving experiences. Results suggest that caregivers sometimes felt emotionally compromised when making objective healthcare decisions, and that 'too much information' resulted in information burden, conflict and a desire to override patient wishes out of compassion and fear. These findings may impact care by illustrating that caregiver involvement should trigger further dialogue between doctors, elderly patients and their caregivers, especially with respect to information sharing boundaries.